CADANGAN PREMI TAHUNAN ASURANSI KESEHATAN PADA STATUS GABUNGAN - Aryo Gunanto; Hasriati '; Rolan Pane (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Health insurance is one type of insurance products that specifically guarantees the cost of health or care insurance when the participants experience health problems and have to stay at the a hospital. This article discusses the amount of annual premium reserve of term health insurance for joint life status using constant force assumption, by first determining the term life annuity, single premium of health insurance and the annual premiums of term health insurance.